Airline management finance : the essentials - Hughes, Victor, 1941- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Airline Management Finance: The Essentials is of significant benefit to airline industry practitioners seeking a focused, neatly contained and accessible resource that provides explicit financial information pertinent to their current or future role. The book explains and de-mystifies an airline's financing and the financial reporting of its operations to airline staff and others. It seeks to explain the role of finance and the Finance Department in a non-technical way, so staff can appreciate the value of the department and its information resources, and see finance as an active contributor to the airline's operation. It concentrates on practical matters, explaining frequently used financial and accounting terms, how financial strategy works, the uses of various types of financial reporting, as well as what financial risk is and how it can be managed through the co-operation of finance and operating staff. Staff who understand the airline's finances and financial system are more likely to make decisions which align with the airline's strategy and objectives. They will also know how to use the financial information which is available. The book establishes a good foundation of financial knowledge for all staff. This book is recommended reading for new employees in airline finance and related areas, as well as those starting to move up the supervisory ladder in an airline"--
OCLC-licensed vendor bibliographic record.
Keywords: Airlines -- Finance; BUSINESS & ECONOMICS / Industries / Transportation; TRANSPORTATION / Aviation / Commercial; TECHNOLOGY / Aeronautics & Astronautics